Solve for a a(a-3)=0

Math
a(a-3)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
a=0
a-3=0
Set the first factor equal to 0.
a=0
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
a-3=0
Add 3 to both sides of the equation.
a=3
a=3
The final solution is all the values that make a(a-3)=0 true.
a=0,3
Solve for a a(a-3)=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top